Type 2 Autoimmune Pancreatitis: A Challenge in the Differential Diagnosis of a Pancreatic Mass - Martins,Cláudio (2017)
Introduction: Autoimmune pancreatitis is a rare entity of unknown etiology that can mimic pancreatic cancer and whose diagnosis involves clinical, serological, imagiological, and histological findings. There are two types of autoimmune pancreatitis: type 1, in which the pancreas is involved as one part of a systemic immunoglobulin G4-related disease, and type 2, generally without immunoglobulin G4-positive cells and without systemic involvement. Case: We report the case of a 45-year-old female, who underwent an abdominal magnetic resonance imaging for etiological study of a solid liver lesion, which revealed a tail pancreatic mass. Laboratory analyses showed normal levels of immunoglobulin G4 and negative antinuclear antibodies. Endoscopic ultrasound revealed a homogeneous and hypoechogenic lesion in the pancreatic tail with a sausage-like appearance. Endoscopic ultrasound-guided fine needle aspiration was inconclusive and the patient underwent a laparoscopic distal pancreatectomy. Histopathology examination confirmed the diagnosis of type 2 autoimmune pancreatitis. Conclusion: This case highlights the challenge in the diagnostic approach of a pancreatic mass, particularly in distinguishing benign from malignant disease.